(untitled) (The Review of Diabetic Studies, 2025)
This study aims to reveal the impact of poor community awareness on the effectiveness of field rescue and ambulance operations at the Saudi Red Crescent Authority, by surveying field workers’ opinions on the behaviors and challenges they face while performing their duties. The study relied on the descriptive analytical approach, and a questionnaire consisting of 20 items was applied to a field sample of 200 field ambulance team workers. The results showed that community members’ poor knowledge of basic first aid, delayed accident reporting, and poor handling of injury sites are among the most prominent challenges affecting the effectiveness of rescue operations. The results also showed that traffic congestion and poor traffic awareness are factors that hinder the rapid arrival of ambulances to accident sites. The study recommended intensifying awareness and training programs in schools, universities, and the media, and activating partnerships between the Red Crescent Authority and educational and community institutions to disseminate a culture of proper handling of field incidents and enhance the speed of response.